Chiari type 1.5 malformation as a cause of secondary trigeminal neuralgia: case report and literature discussion - Ergun, Ahmet Cemil; Ertugrul, Bilal; Yildirim, Gokhan; Kaplan, Metin (Springernature, 2024)
Background Chiari syndrome is a very rare cause of secondary trigeminal neuralgia (TN). There are a few cases of TN associated with Chiari syndrome in the literature, and all of these cases were reported as Chiari type 1. In this report, we present a case of secondary trigeminal neuralgia caused by Chiari type 1.5 for the first time unlike the literature.Case presentation A 38-year-old male patient, who had frequent and severe attacks of pain under the orbit, at the chin and rim of the mouth, was evaluated with craniocervical Magnetic Resonance Imaging (MRI) and revealed Chiari type 1.5 malformation and syringomyelia.Conclusions The mechanism of TN associated with Chiari malformation is unclear. However, the main concepts emphasized in cases presented in the literature are compression and stretching. The rapid relief of pain after decompression surgery in these cases also supports this situation. It can be predicted that compression and tension forces will become more pronounced in Chiari type 1.5 malformation, in which the brainstem elongation and ventral pressure are more prominent. Decompression of the foramen magnum provides rapid and effective pain control in the treatment of TN accompanying Chiari 1.5 syndrome that does not respond to medical treatment.
Keywords: Trigeminal neuralgia; Chiari tip 1.5 malformation; Syringomyelia; Suboccipital decompression